Critical Appraisal to Intraabdominal and Complicated Intraabdominal Guidelines to Develop Indonesian Specific Clinical Practice Guidelines - Moenadjat, Yefta; Mulya, Dina D.; Lalisang, Toar JM. (UI Scholars Hub, 2017)
Introduction. There were many clinical practice guidelines (CPG) intraabdominal infection/complicated intraabdominal infections (cIAI) have been developed since 1992 and were periodically updated recently. But to date, the implementation in Indonesia encountering problems. One is Indonesian characteristics which is differed to the population of where the CPG developed. To adapt a CPG, the quality of CPG should be first critically appraised. The best will be used furthers as the subject to be adapted, with modification regarding Indonesian characteristics. Method. A literature search carried out on guidelines databases to find out CPG on cIAI (1992–2017). The assessment preceded using AGREE II tools (MyAGREE platform) focused on 23 assessments in 6 domains (scope and purpose, stakeholder involvement, rigour of development, clarity of presentation, applicability, and editorial independence). Such an assessment placed a guideline in rating of 1 to 7. Updated guidelines were assessed using Checklist for the Reporting of Updated Guidelines (CheckUp). Appraised CPG were discussed. Results. There were 33 CPG in full text downloaded and subjected to selection criteria. Duplicates and those irrelevant were excluded. In the assessment there were 18 CPG included and 13 guidelines places the strong recommended category, two can be recommended and other 2 were not recommended. All updated CPG met the criteria of the best quality updates. Conclusion. Two cIAI–CPG were met the criteria of the quality guidelines to be adopted. These guidelines were developed in accordance with appropriateness in development a CPG and were updated.